Finger-Photoplethysmography: Intensive Development and Validation for Noninvasive Measurement of Blood Glucose - Dao, Viet Hung (Old Journal, 2019)
This paper presents a specialized design and intensive validations for measuring blood glucose using photoplethysmography with pulsed light. Glucose level is an important index because whose excess can cause serious complications. Photoplethysmography had been introduced as a potential method for daily monitoring glucose level. Following the trend, most of the published studies focused on identifying the correlation between the glycemic index and infrared light absorption. However, the simple measurement system limits the development of the potential technique. This paper presents a specialized design and intensive validations to apply and verify the use of pulsed light sources for developing more feasible measurement devices. Experimental results not only confirmed applicabilities of the new design with modulated light, but also exhibited remarkable phenomena and notable parameters for error prevention. Hence, this research could contribute useful reference for further studies.